Features of wave excitation of the electrostatic ion cyclotron type in the auroral ionosphere - Chernyshov, A. A.; Ilyasov, A. A.; Mogilevsky, M. M.; Golovchanskaya, I. V.; Kozelov, B. V. (Cosmic research, 2016)
Broadband electrostatic noise in the auroral ionosphere can be identified as a version of waves of an electrostatic ion cyclotron type, excited by plasma instability resulting from an inhomogeneous distribution of wave energy density. Broadband waves are generated due to both electric field inhomogeneities and plasma density inhomogeneities. The effect of the form of the distribution of electric field and plasma density inhomogeneities on the excitation of instabilities is studied. Also there is shown the role of the characteristic scale of inhomogeneities in the generation of electrostatic ion cyclotron waves due to the development of instability of this kind. The study of these issues, which are important for understanding the processes in the auroral region, is the subject of this paper. The work presents also a comparison of numerical results obtained using both satellite data and model approximations.